Identification: a new Archival Science function? - Rodrigues, Ana Célia (2021)
This study presents the archival identification processes, especially about the identification of documents developed by documental typology parameters. The identification is a search procedure on the archival document and its producer entity that uses intelligence to search and records data with adequate instruments. This technique is developed in the beginning of the documental treatment to fundament the analysis related to the production, appraisal, classification and description of the document. The research aims to launch a theoretical basis for characterizing the identification as an independent function within the archival methodology, systematizing it in the perspective of the archival tradition in Brazil. Combines a theoretical dimension to an applied, presenting case studies on the applicability of the methodology in the context of document management and treatment of mass accumulated in archives.